Cruise tourism externalities and residents' support: A generalized ordered logit analysis - Juan Gabriel Brida; Giacomo Del Chiappa; Marta Meleddu; Manuela Pulina (Kiel Institute for the World Economy (IfW), 2012)
This paper investigates residents' preferences towards cruise tourism investment in their home port. The research uses data collected during the peak cruise season in 2011 at Messina, a port of call in Sicily, Italy. A generalized ordered logit analysis is run to analyse what factors influence the residents' preferences towards investment in cruise tourism. Positive and negative externalities produced by this economic activity, as well as socio-demographic and economic determinants are taken into account. Overall, the resource investment choice of residents in Messina was dependent upon: their income dependency on the cruise activity, their own personal cruise experience, family size, the expected increase in welfare (i.e. increase in public and private investment), whether they are affected by urban and rural gentrification and the value placed on community life style and heritage conservation. Nevertheless, residents would tend to decrease investments in cruise activity if they are female, retired or perceive the environment to be deteriorating. Implications for policy makers are drawn from the empirical findings.
Keywords: C25; D62; L83; 330; Cruise port of call; positive and negative externalities; residents' support; generalized ordered logit